Optimizing Tax Aggressiveness: Unraveling The Impact Of Liquidity, Profitability, Leverage, Firm Size, Inventory Intensity, and Capital Intensity - Purwantoro, Purwantoro; Entot Suhartono; H. S, Dian Festiana (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study examines whether liquidity, profitability, leverage, company size, capital intensity, and inventory intensity influence companies' tax aggressiveness or tax avoidance. This research uses secondary data taken from the annual financial statements of food and beverage sector companies listed on the IDX during the 2019-2023 period. After going through the calculation and selection of samples, 17 companies were obtained during five observation periods. Hence, the sample of financial statements tested in this study was as many as 85 financial reports. The methods used are descriptive analysis, classical assumption test, multiple linear regression test, and model feasibility test. The results of this study show that liquidity, profitability, company size, and capital intensity affect corporate tax aggressiveness or tax avoidance. Leverage and inventory intensity do not influence tax aggressiveness or tax avoidance.